Bordetella pertussis adenylate cyclase toxin modulates innate and adaptive immune responses: distinct roles for acylation and enzymatic activity in immunomodulation and cell death - LAVELLE, EDWARD; MILLS, KINGSTON (The American Association of Immunologists, 2005)
Adenylate cyclase toxin (CyaA) of Bordetella pertussis belongs to the repeat in toxin family of pore-forming toxins, which require posttranslational acylation to lyse eukaryotic cells. CyaA modulates dendritic cell (DC) and macrophage function upon stimulation with LPS. In this study, we examined the roles of acylation and enzymatic activity in the immunomodulatory and lytic effects of CyaA. The adenylate cyclase activity of CyaA was necessary for its modulatory effects on murine innate immune cells. In contrast, acylation was not essential for the immunomodulatory function of CyaA, but was required for maximal caspase-3 activation and cytotoxic activity. The wild-type acylated toxin (A-CyaA) and nonacylated CyaA (NA-CyaA), but not CyaA with an inactive adenylate cyclase domain (iAC-CyaA), enhanced TLR-ligand-induced IL-10 and inhibited IL-12, TNF-, and CCL3 production by macrophages and DC. In addition, both A-CyaA and NA-CyaA, but not iAC-CyaA, enhanced surface expression of CD80 and decreased CpG-stimulated CD40 and ICAM-1 expression on immature DC. Furthermore, both A-CyaA and NA-CyaA promoted the induction of murine IgG1 Abs, Th2, and regulatory T cells against coadministered Ags in vivo, whereas iAC-CyaA had more limited adjuvant activity. In contrast, A-CyaA and iAC-CyaA induced caspase-3 activation and cell death in macrophages, but these effects were considerably reduced or absent with NA-CyaA. Our findings demonstrate that the enzymatic activity plays a critical role in the immunomodulatory effects of CyaA, whereas acylation facilitates the induction of apoptosis and cell lysis, and as such, NA-CyaA has considerable potential as a nontoxic therapeutic molecule with potent anti-inflammatory properties.
PUBLISHED
Keywords: Biochemistry